If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-14-8x=-(
We move all terms to the left:
-14-8x-(-()=0
We add all the numbers together, and all the variables
-8x=0
x=0/-8
x=0
| 12+5x-8=12x+14 | | 28+8x=8(x=3)+2 | | 9x−1=26 | | 12x+48=79 | | 5b+40=12b | | -13+b=3b-1 | | 8x−8=44 | | (8x-25)=(7x-5)=180 | | -2-7z=-19-2z-6z | | 5^2x+5^x+1-50=0 | | X+4+3x=18 | | 6x-2(3x+8)=-16 | | A40=-1191,d=-30 | | 20+13c=5+12c | | 23x-(5x+10)=15x+24 | | ((x-48)^{1/2})^{2}=x^{0} | | 20+.50x=2x | | -12-d=d | | Ax+5=13 | | A1=28,d=10* | | 535x=55+x | | 3^(1-6x)=4x | | 4x+13=25* | | 35+x=55x | | 9-3r=-2r-3-5r | | -2.7=6+3c | | X+7+13=5x-1 | | 4+3d=4+3d+10d | | x+(x+2)=94 | | 9a-4=3(3a-4) | | 2x-8=-5x+20 | | -t/4-4=3.1 |